2021
DOI: 10.2147/ott.s287064
|View full text |Cite
|
Sign up to set email alerts
|

A Case Report: Cutaneous Metastasis of Advanced Rectal Cancer with BRAF Mutation

Abstract: Cutaneous metastasis of rectal cancer is rare and typically indicates widespread disease and poor prognosis. We report an exceedingly rare case of BRAF-mutated MSS rectal cancer with metastasis to the skin. A 53-year-old woman presented with stage IV unresectable adenocarcinoma of the rectum and received chemotherapy and molecularly targeted agents. Six months later she developed a focal skin nodule in the left groin. During treatment with four cycles of FOLFIRI plus bevacizumab, the skin nodules gradually inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…Christensen et al reported that the BRAF V600E mutation is associated with an increased risk of cutaneous metastases [40]. Although a few cases of cutaneous metastasis of BRAF-mutant CRC have been reported in fact, the number is small, and further accumulation of cases is needed to explore the relationship between BRAF mutation and cutaneous metastasis [12,20,41]. Yunoki et al reported the first case of cutaneous metastasis of CRC that was MSI-H and BRAF V600E-mutant [42].…”
Section: Discussionmentioning
confidence: 99%
“…Christensen et al reported that the BRAF V600E mutation is associated with an increased risk of cutaneous metastases [40]. Although a few cases of cutaneous metastasis of BRAF-mutant CRC have been reported in fact, the number is small, and further accumulation of cases is needed to explore the relationship between BRAF mutation and cutaneous metastasis [12,20,41]. Yunoki et al reported the first case of cutaneous metastasis of CRC that was MSI-H and BRAF V600E-mutant [42].…”
Section: Discussionmentioning
confidence: 99%
“…However, certain subsets of metastatic colorectal cancer may also lose expression of CDX2. 34,35 Primary cutaneous mucinous carcinoma also expresses other cytokeratins (AE1/AE3, CAM5.2) as well as epithelial membrane antigen (EMA), carcinoembryonic antigen (CEA), estrogen receptor (ER), progesterone receptor (PR), and GCDFP-15. 19,26,36,37 The expression of multiple breast markers (ER, PR, and GCDFP-15) makes PCMC difficult to differentiate from metastatic breast cancer on histopathologic and immunohistochemical grounds alone.…”
Section: Histopathologymentioning
confidence: 99%
“…Different conditions that may appear similar to skin metastases include cysts, lipomas, granulomas, and neurofibromas. So, it is very important to do a biopsy of any suspicious cutaneous lesion [4]. In this case report, we will talk about the clinical presentation and imaging findings of cutaneous metastases during the treatment of advanced rectal cancer.…”
Section: Introductionmentioning
confidence: 99%